Cylinder-to-cylinder variation sources in diesel low temperature combustion and the influence they have on emissions. (January 2014) - Bittle, Joshua; Zheng, Junnian; Xue, Xingyu; Song, Hoseok; Jacobs, Timothy
Cylinder-to-cylinder variation in a multi-cylinder diesel engine was found to increase substantially when transitioning to a low-temperature combustion mode. This study was started to investigate the potential influence this effect could have on the emissions levels. Initial testing showed an imbalance in the fuel distribution that prompted this article to focus on data from before and after swapping two injectors under both conventional and low-temperature combustion modes. A significant improvement is observed in cylinder variation based both on visual heat release inspection and on mean effective pressure variation. This is likely a result of a changing combination of exhaust gas recirculation and fuel distribution such that less cylinder-to-cylinder variation is present (e.g. high dilution and low fuel, switched to low dilution and low fuel). Interestingly, despite the reduced cylinder-to-cylinder variation, the results show that the emissions levels are actually not affected. Despite the lack of influence on emissions results, the cylinder-to-cylinder variation in low-temperature combustion modes is still a critical factor that could impact its ability to be implemented in a commercial setting. Further cylinder balancing was attempted and achieved by introducing small (microsecond) adjustments to each cylinder start of injection and injection duration. The balancing is effective, but due to exhaust gas recirculation imbalance, a single adjustment setting does not apply to both conventional and low-temperature combustion modes. Additionally, day-to-day ambient conditions also negate the effectiveness. This supports the idea that some type of consumer-based real-time automatic balancing system may be needed in the future.